Takaful and Mutual Insurance : Alternative Approaches to Managing Risks - Gönülal, Serap O. (Washington, DC: World Bank, 2013)
Access to insurance, as part of a broad range of essential financial services, is especially important for poor households in order to smooth consumption, build assets, absorb shocks, and manage risks associated with irregular and unpredictable income. Without access to good formal insurance services, the poor depend on less reliable and often far more expensive informal sector mechanisms. Yet, in many majority Islamic countries, accessing and using insur-ance products has been quite limited, as many Muslims avoid such services over concerns about riba (interest), gharar (uncertainty and ambiguity in contracts), and maysir (speculative risk), among other factors. Takaful insurance products are emerging as a central part of the Shariah-compliant family of financial services, helping meet insurance needs in ways that are consistent with the local norms and beliefs of many majority Islamic countries. Takaful has been developing steadily since the first Shariah-compliant insurer was founded in 1979, based on a Shariah-compliant cooperative model resembling mutual insurance. This is based on a group of participants donating funds into a pool that members can then use in the event of specified unfavorable contingencies. While practitioners have applied varying business models and standardization remains a challenge, many policy makers recognize the potential of takaful to expand financial inclusion and have aimed to promote the industry with supportive legislation and effective regulation. The response has been strong, with premiums growing about 30 percent (inflation adjusted) annually between 2007 and 2010, reaching US$8.3 billion. This robust performance is expected to continue, based on substantial latent demand in Muslim majority countries and improvements in the industry, including better distribution capabilities.